Character Design of Indonesian Chinese Youth for Webtoon “Kenangan Angpao” - Tanlia Gunawan; Alfian Candra Ayuswantana; Aileena Solicitor CostaRiza El Chidtian (Gorga : Jurnal Seni Rupa, 2026)
Chinese New Year celebrations hold significant cultural importance in China, embodying traditional values and symbolic meanings. However, the advent of globalization has led to a decline in the understanding of Chinese New Year culture among younger generations. Visual media, particularly webtoons, present a promising avenue for cultural introduction tailored to the characteristics of contemporary youth. This study seeks to design webtoon characters that embody the essence of Chinese New Year and represent young Chinese Indonesians in the context of modern life. The methodology employed in this study involves a structured design process encompassing pre-production, production, and post-production stages. The outcomes of this study are webtoon character designs that effectively convey the identity, lifestyle, and personality of young Chinese Indonesians. It is anticipated that this design serves as an alternative medium for introducing Chinese New Year culture, fostering greater relevance and acceptance among the younger generation.